Youth services participation of youth - youth policy in Hungary 2006-2012 - Jancsák Csaba (Belvedere Meridionale, 2013)
Hungary’s youth context changed in 2006, before the world crisis, and recession has spread since then. Youth institutions have gone through constant changes which are difficult to follow, aft er six years almost none of them are left . Youth resources have decreased both on the local and on the national level, due to mutually reinforcing economic and political eff ects. During the examined period, the proportion of youth tolerating more violent behaviour has increased, as well as those longing for strong leaders and those disillusioned with capitalism. Nowadays, apart from lobbying, demonstrations, elaborating independent political alternatives, a new, rational behaviour appears among youth, the phenomenon of leaving the country.